Briefly Describe the Historical Evolution of Western Aesthetic Thought — Take Zhu Guangqian’s History of Western Aesthetics as a Reference - Minwen Lu (Art and Society, 2023)
Zhu Guangqian’s History of Western Aesthetics provides a valuable framework for understanding the historical evolution of Western aesthetic thought. It illustrates how various philosophers, artists, and movements have shaped and reshaped our understanding of beauty, art, and the role of aesthetics in Western culture.